ANALISIS MODEL GROVER, SPRINGATE DAN ZMIJEWSKI SEBAGAI PREDICTOR FINANCIAL DISTRESS PADA PERUSAHAAN RETAIL YANG TERDAFTAR DI BEI TAHUN 2016-2019 - - Marli; - Widanarni (SEKOLAH TINGGI ILMU EKONOMI NASIONAL (STIENAS) BANJARMASIN, 2021)
Abstract, This research aims to compare the use of financial distress prediction models and the accuracy of their predictions. The models used to predict financial distress are the Grover, Springate and Zmijewski models. Accuracy of using the model is done by comparing the predictions of each model with the net profit of each company. The data in this research are in the form of annual financial reports published by the company on the Indonesian Stock Exchange website. The sample used is retail companies listed on the IDX during 2016-2019. Sampling was done by purposive sampling technique with a total sample of 5 companies, namely companies coded MPPA, HERO, RALS, ACES and AMRT shares. The results show that the Springate and Zmijewski models are predictive models with a high degree of accuracy, namely 95% each and an error rate of 5% each. Meanwhile, the Grover model has 90% accuracy in detecting retail financial distress with an error rate of 10%.